Nitric oxide and phytoglobin PHYTOGB1 are regulatory elements in the Solanum lycopersicum-Rhizophagus irregularis mycorrhizal symbiosis - Martínez-Medina, Ainhoa (The New phytologist, 2019)
© 2019 The Authors. New Phytologist © 2019 New Phytologist Trust.